Institutions, Firms and Economic Growth - Jane Frances (New Zealand Government, The Treasury, 2004)
This paper reviews the literature on institutions and explores the ways in which institutions can influence economic growth, with a particular focus on how institutions affect the use that firms make of human capital to improve their productivity. It discusses the influence of underlying institutions, such as law and order and secure property rights, on the general environment within which the economic activities of production and exchange takes place. It also explores the influence of activity-specific institutions, such as labour market institutions, on firm decisions about resource use and innovation and through these on economic activity and economic growth.
Keywords: D00; D20; J24; K00; L51; O40; P00; Z1; 330; institutions; human capital; regulation; norms; firms; economic growth; New Zealand